YOLO-CFruit: a robust object detection method for Camellia oleifera fruit in complex environments - Luo, Yuanyin; Liu, Yang; Wang, Haorui; Chen, Haifei; Liao, Kai; Li, Lijun (Frontiers in Plant Science, 2024)
Introduction In the field of agriculture, automated harvesting of Camellia oleifera fruit has become an important research area. However, accurately detecting Camellia oleifera fruit in a natural environment is a challenging task. The task of accurately detecting Camellia oleifera fruit in natural environments is complex due to factors such as shadows, which can impede the performance of traditional detection techniques, highlighting the need for more robust methods. Methods To overcome these challenges, we propose an efficient deep learning method called YOLO-CFruit, which is specifically designed to accurately detect Camellia oleifera fruits in challenging natural environments. First, we collected images of Camellia oleifera fruits and created a dataset, and then used a data enhancement method to further enhance the diversity of the dataset. Our YOLO-CFruit model combines a CBAM module for identifying regions of interest in landscapes with Camellia oleifera fruit and a CSP module with Transformer for capturing global information. In addition, we improve YOLOCFruit by replacing the CIoU Loss with the EIoU Loss in the original YOLOv5. Results By testing the training network, we find that the method performs well, achieving an average precision of 98.2%, a recall of 94.5%, an accuracy of 98%, an F1 score of 96.2, and a frame rate of 19.02 ms. The experimental results show that our method improves the average precision by 1.2% and achieves the highest accuracy and higher F1 score among all state-of-the-art networks compared to the conventional YOLOv5s network. Discussion The robust performance of YOLO-CFruit under different real-world conditions, including different light and shading scenarios, signifies its high reliability and lays a solid foundation for the development of automated picking devices.